2022
DOI: 10.1088/1402-4896/ac690e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fe2O3/Al addition on the neutron shielding, microstructure, thermal, and mechanical properties of HDPE composites

Abstract: High-density polyethylene (HDPE) has been reinforced with various ratios of iron oxide (-Fe2O3) and aluminum (Al) nanoparticles (NPs) to be used as shielding materials against nuclear radiation. The examination of scanning electron microscopy images (SEM) reveals small polymeric agglomerations besides the uniform dispersion of Al and -Fe2O3 NPs. Also, all stress parameters (i.e σ_Y,σ_M,and σ_f) decremented after incorporating the 40 wt.% -Fe2O3 NPs into the HDPE matrix. Meanwhile, the mutual additions of Al po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Thermal degradation is associated with the recycling process, which can be attributed to a change in the molecular weight without forming volatile products, resulting from the cleavage of weak links, such as oxygen bridges and lateral chains [ 20 ]. Several authors have reported that the heating applied during the recycling and pelletizing process can favor the formation of shorter chains in the HDPE samples, which are less thermally stable than virgin material [ 46 , 51 , 54 ]. Figure 6 also shows minor differences in the thermal degradation profiles, especially in the maximum thermal degradation rate (minimum of the curve), which is slightly lower for recycled polymers with Cu-NPs than virgin polymers with Cu NPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal degradation is associated with the recycling process, which can be attributed to a change in the molecular weight without forming volatile products, resulting from the cleavage of weak links, such as oxygen bridges and lateral chains [ 20 ]. Several authors have reported that the heating applied during the recycling and pelletizing process can favor the formation of shorter chains in the HDPE samples, which are less thermally stable than virgin material [ 46 , 51 , 54 ]. Figure 6 also shows minor differences in the thermal degradation profiles, especially in the maximum thermal degradation rate (minimum of the curve), which is slightly lower for recycled polymers with Cu-NPs than virgin polymers with Cu NPs.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 7 reveals a drastic effect on the mechanical properties of the HDPE from the recycling process, such as the maximum tensile strength , the tensile strength at break ( ), elongation at break ( ), and shore D hardness (D), as also shown in Table 2 . The properties of the virgin HDPE were degraded by the recycling process but enhanced by the addition of Cu particles, which can be associated with a modification of complex polymeric chains during the tension processes [ 54 , 56 ]. Figure 7 and Table 2 show that the maximum strength decreased slightly with the recycling process compared to the virgin sample that increased with the addition of Cu-NPs and Cu-NCs.…”
Section: Resultsmentioning
confidence: 99%
“…The statistical error associated with the measurements was in the range of 5% with a measuring time of 600 s for each run. The errors in the values of μ, m D , ( ) were calculated from the errors associated with the measured parameters I , 0 I, and x according to the following equation [73][74][75][76]:…”
Section: Gamma-ray Shielding Parameters and Experimental Proceduresmentioning
confidence: 99%
“…Neutron radiation finds applications in various fields, including synthesizing radioisotopes for medical diagnosis and treatment, healthcare, and aerospace. Neutron radiation protection depends on using shielding materials to safeguard personnel and the environment against detrimental consequences [1,2]. The selection of the shielding material depends on how the nuclei interact with the incoming radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Iron and/or iron oxide as fillers incorporated into various composites for radiation shielding were investigated in different studies. The results indicated that the attenuation capacity of the prepared composites was enhanced compared with the traditional shielding materials [2,[48][49][50][51][52]. Aluminum and/or aluminum oxide have been investigated as fillers to improve the mechanical properties and radiation shielding effectiveness for different matrix composites.…”
Section: Introductionmentioning
confidence: 99%